"A Unique and Forward-Looking Sector": Reflecting on 30 Years of Community Access Radio in Aotearoa New Zealand. Issue 1 (2nd January 2021) - Beatty, Bronwyn; Pauling, Brian
ABSTRACT: This article reflects on 30 years of Community Access Radio (CAR) in Aotearoa New Zealand. This sector was championed by the state in 1989 to counteract the radical deregulation of the radio market at that time. CAR has since become an integral part of the national mediascape, navigating substantial changes in technology and audience practices, responding to extraordinary events and surviving despite increasingly constrained financial circumstances. All this has been achieved while going about the daily business of efficiently and effectively enabling minority voices within the community to broadcast their messages.